A New Reconfiguration Method for PV Array System - Parlak, Koray Sener (Ieee, 2013)
In this study, a method that reconfigures the connection structure of photovoltaic panels has been suggested. It has been applied under partial shading conditions in order to increase the power gained from the photovoltaic array. In the presented method, all submodules of array are formed with the panels that have similar insolation as far as possible. For that purpose, the possibilities of connection structures that are likely to be in the array are found with the configuration scanning algorithm. The connection structure of array is reconfigured by using short circuit currents, which are taken from particular parts of array in this scanning algorithm. In Matlab-Simulink environment, reconfiguration method on an array which is suggested under partial shading conditions has been tested. It is seen that efficiency of the array has considerably increased with the presented reconfiguration method.
39th Annual Conference of the IEEE Industrial-Electronics-Society (IECON) -- NOV 10-14, 2013 -- Vienna, AUSTRIA
Keywords: PV systems; PV array reconfiguration; maximum power point transfer; partial shading condition